An International Comparison of Baseline Characteristics of Patients Undergoing Initiation of Anti-VEGF Therapy for DME - Conti, Felipe F.; Alezzandrini, Arturo; Rasendran, Chandruganesh; Nakhwa, Chinmay; Neves, Diogo; Queiroga, Fabiana S.; Chhablani, Jay; Rocha, Jorge; Martins, Ramon P.; Romero, Jose; Wu, Lihteh; Han, Michael; et al. (Ophthalmic surgery, lasers & imaging, 2019)
Diabetic macular edema (DME) is a leading cause of vision loss worldwide. The object of this study is to compare global differences of baseline characteristics of patients undergoing initiation of anti-vascular endothelial growth factor (VEGF) therapy for DME. This multicenter, cross-sectional study included diabetic patients with foveal-involving retinal edema secondary to DME as documented by fundus exam and optical coherence tomography who were undergoing initiation of intravitreal anti-VEGF drugs. Variables were collected to find possible risk factors and to create an epidemiological profile of DME patients undergoing initiation of anti-VEGF agents. Nine hundred two patients were selected. Mean age was 62.4 (±11) years, 49.7% were Caucasians, 57.6% were male, and 96% had type two diabetes with an average disease duration of 181.7 months ± 113 months. Of the patients included, 74.7% suffered from hypertension, 26.6% from cardiovascular disease, 12.1% from cerebrovascular disease, 12.8% from peripheral vascular disease, and 12.8% from renal insufficiency. Best-corrected visual acuity (BCVA) was 65 (±20) Early Treatment Diabetic Retinopathy Study letters, central subfield thickness was 364 (±162) μm, cube volume 11.1 ± 3.1 mm , cube average thickness 328.8 μm ± 61 μm, and 63.9% had nonproliferative diabetic retinopathy. Comparison between U.S. versus international patients, and patients with BCVA 70 letters or less versus more than 70 letters were performed, significant differences were acknowledged, and risk factors were recognized. There were key differences in the epidemiologic profile between patients presenting with DME in the U.S. and internationally. [Ophthalmic Surg Lasers Imaging Retina. 2019;50:e300-e310.].